2013
DOI: 10.5897/ajpp2013.3449
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive, cytological and biochemical toxicity of fenugreek in male Swiss albino mice

Abstract: Fenugreek was evaluated for its effects on reproductive, cytological and biochemical toxicity in mice.On the basis of evaluated maximum tolerated dose (MTD; 9.77 g/kg), the present doses selected for sub-chronic (90 days) treatment were 153, 305 and 610 mg/kg/day by oral gavage corresponding to 1/64, 1/32 and 1/16, of MTD, respectively. Total sperm count, motility and spermatozoa morphology was screened. Cytological changes in testicular chromosomes and pregnancy rate in untreated females after mating with tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“… Trigonella arabica Reported in India, Africa [ 54 ], and Egypt [ 55 ]. Treatment of inflammation [ 56 ] Administration at higher dose induced toxicity including teratogenic, foetotoxic, reproductive changes and the abnormal shapes of the sperms [ 57 ] Prunus dulcis Reported in Iraq [ 58 ] and Lebanon [ 59 ] and well known Worldwide High antioxidant activity [ 60 ] and used for premature hair fall [ 61 ] No reference Citrus limon Reported throughout the world [ 62 ] Skin care and anti-oxidants [ 62 ]. No reference Pimpinella anisum Reported in Mediterranean Region [ 63 ], Palestine [ 64 ], the Middle East [ 65 ] and Spain [ 63 ] Reported to have insecticidal effect [ 66 ], antioxidant and anti-inflammatory effect [ 67 ], No reference Punica granatum Reported in India [ 68 ], Algeria [ 69 ], Africa [ 70 ], America [ 71 ], Spain [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“… Trigonella arabica Reported in India, Africa [ 54 ], and Egypt [ 55 ]. Treatment of inflammation [ 56 ] Administration at higher dose induced toxicity including teratogenic, foetotoxic, reproductive changes and the abnormal shapes of the sperms [ 57 ] Prunus dulcis Reported in Iraq [ 58 ] and Lebanon [ 59 ] and well known Worldwide High antioxidant activity [ 60 ] and used for premature hair fall [ 61 ] No reference Citrus limon Reported throughout the world [ 62 ] Skin care and anti-oxidants [ 62 ]. No reference Pimpinella anisum Reported in Mediterranean Region [ 63 ], Palestine [ 64 ], the Middle East [ 65 ] and Spain [ 63 ] Reported to have insecticidal effect [ 66 ], antioxidant and anti-inflammatory effect [ 67 ], No reference Punica granatum Reported in India [ 68 ], Algeria [ 69 ], Africa [ 70 ], America [ 71 ], Spain [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the Klimisch categories of ToxRTool, the category code of these 391 (89.67%) studies were “4” which indicates that a paper is “not assignable” because it does not contain any primary data. Remaining 45 (10.33%) studies were included for quantitative analysis by ToxRTool [6, 7, 8, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have investigated multifaceted therapeutic benefits of fenugreek seeds against a variety of ailments including diabetes, cancer, hyperlipidemia, inflammation, neurotoxicity, hepatotoxicity, ulcers, wound, bacterial and fungal infections, weakness, and edema of the legs [4, 5]. Apart from its beneficial effects, many studies have also documented its toxicological profile [6, 7, 8]. However, these published literature are diverse in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the toxicological impact of this plant on reproduction. In fact, the study by Al-Yahya [20] demonstrated that fenugreek administration to males mated with untreated females induces teratogenic, foetotoxic, and reproductive changes and the abnormal shapes of the sperms. Other studies show that these seeds have an estrogenic activity that disturbs the endometrial lining system and interferes with fetal development [21,22].…”
Section: Introductionmentioning
confidence: 99%